Investigation of γ′-Fe 4 N−GaN Nanocomposites: Structural and Magnetic Characterization, Mössbauer Spectroscopy and Ab Initio Calculations - Kurian, Sajith (2010)
A controlled, one-step ammonolysis method with three different Fe/Ga ratios (70:30, 50:50, and 30:70) was used to synthesize functional nanocomposite materials consisting of 30-40 nm particles of γ′-Fe4N Fe4-xGaxN phases in a GaN and Fe-doped GaN phase matrix. The γ′-Fe4N, Fe4-xGaxN, and GaN phases were confirmed by the Rietveld analysis of the X-ray diffraction patterns, and the Fe-doped GaN phase was confirmed from Mo¨ssbauer spectroscopy and magnetization measurements. The magnetization of the superparamagnetic nanoparticles was expectedly reduced with the Ga incorporation in the samples. The coexistence of antiferromagnetic Fe4-xGaxN and the ferromagnetic γ′-Fe4N phases resulted in an exchange bias effect (hysteresis loop shift of 28 Oe at 5 K) and a gradual magnetic phase transition from 250 to 55 K. Mo¨ssbauer spectroscopic analysis showed a hyperfine magnetic field distribution that the ab initio calculations duly supported. Ab initio calculations of the equilibrium lattice and Mo¨ssbauer hyperfine parameters were also performed.